Convention on a common transit procedure, Interlaken, 20 May 1987 : Council Decision on the position to be taken on behalf of the European Union with the EU-CTC Joint Committee established by the Convention of 20 May 1987 on common transit procedure, as regards amendments to that Convention, Brussels, 25 September 2018 /: Council Decision on the position to be taken on behalf of the European Union with the EU-CTC Joint Committee established by the Convention of 20 May 1987 on common transit procedure, as regards amendments to that Convention, Brussels, 25 September 2018. ([2018-12-05]) - Unknown
No abstract available